Gender, Salary and Promotion in the Academic Profession - Melanie E. Ward (Institute for the Study of Labor (IZA), 2000)
This paper examines the hypothesis that the gender salary gap observed in the academic labour market is predominantly explained by the differing average characteristics of male and female academics and barriers to female promotion. Preliminary analysis reveals that the crowding of women into the lower rungs of academia is a strong determinant of their lower average salary. This effect should be transitory as young women, now entering the profession, move up its ranks. We construct a rank attainment model and investigate the current and predicted distribution of females across ranks. Significant evidence of barriers to female promotion is revealed.
Keywords: J70; J44; 330; Academic profession; gender discrimination; promotion; salary; Akademische Berufe; Geschlecht; Erwerbsverlauf; Lohndifferenzierung; Arbeitsmarktdiskriminierung; Schätzung; Großbritannien; Schottland